USE OF EDUCATIONAL GAME WEBSITE MEDIA IN ONLINE LEARNING ON STUDENT'S CRITICAL THINKING - Lidiya Septiyani; Aiman Faiz; Dewi Yuningsih; Bagus Nurul Iman (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2021)
The existence of an online learning process that is very monotonous and less attractive and it makes students less concentrated and passive. An interesting learning process can make students enthusiastic and active in an online learning activity. The purpose of this study is to determine the formation of students' critical thinking power in online learning by using educational game website media, for examples quizizz media and crossword puzzles so the students are able to express critical thinking power with website-based game media. This research is a type of qualitative research with the subject of students and teachers of class V SD Negeri Kartini IV Kota Cirebon. The techniques used to collect data are interviews, observation, documentation. Data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. The result of this research is the existence of critical thinking power by using educational game website media, for examples quizizz media and crossword puzzles in fifth grade students of SD Negeri Kartini IV Kota Cirebon. The average in the results of this study is that when using the two media, they can think critically with different results in each medium. This is evidenced by researching using critical thinking indicators on educational game website media.